Morphological and biological characteristics and distribution of the powdery mildew fungus Erysiphe circaeae L. Junell in Belarus - Fiadziushka Ilya А.; Khramtsov Аlexander K. (Experimental Biology and Biotechnology, 2024)
In the course of the studies, it was established that on the territory of republic, in the Southern and New agroclimatic regions, the powdery mildew fungus Erysiphe circaeae L. Junell on the Circaea lutetiana L. undergoes a development cycle, including both anamorph and teleomorph. For the first time the morphometric characteristics of the asexual and sexual development stages of the powdery mildew causative agent on broad-leaved enchanter’s nightshade are studied using material from Belarus. Such information has not been published previously. The strict preferences of the fungi E. circaeae and E. howeana U. Braun with their host plants – C. lutetiana and Oenothera biennis L. respectively – is shown on the вases of comparative analysis of the conidia size. The herbophilic mycosinusia composition with the participation of the fungus E. circaeae is reviewed and the estimated localities of its occurrence on representatives of the genus Circaea in Belarus are indicated.